The Development of Past Tense Forms in Albanian Native Speakers and Learners of English as a Second Language - Këpuska, Arta (Advances in Social Sciences Research Journal, 2024)
This study explores how Albanian learners acquire tense-aspect systems, focusing on two distinct groups: adult learners of English as a Second Language (ESL) and young native speakers of Albanian. Drawing on the Aspect Hypothesis (AH), which asserts that the aspectual properties of verbs play a key role in the acquisition of tense-aspect distinctions, the research aims to determine if these learners exhibit universal patterns in their development. Data was collected through written tasks, narrative exercises, and demographic questionnaires from Albanian bachelor’s students and children in grades 2-5. The analysis reveals that Albanian ESL learners demonstrate more variability and complexity in their past tense use, while young native speakers show a more systematic and predictable pattern, consistent with AH predictions. The study provides new insights into how the Aspect Hypothesis operates across different age groups and language contexts, offering valuable recommendations for improving teaching approaches and curriculum design for Albanian ESL learners.